Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.4236/acs.2014.41013
|View full text |Cite
|
Sign up to set email alerts
|

Wind Power Potential in Interior Alaska from a Micrometeorological Perspective

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…Obviously, Equation 1does not explicitly depend on thermal stratification. As pointed out by [8], the vertical wind-profile function shows such a dependency. Being located in a steep valley (Figure 1), inversions frequently occur at Juneau.…”
mentioning
confidence: 74%
See 3 more Smart Citations
“…Obviously, Equation 1does not explicitly depend on thermal stratification. As pointed out by [8], the vertical wind-profile function shows such a dependency. Being located in a steep valley (Figure 1), inversions frequently occur at Juneau.…”
mentioning
confidence: 74%
“…We applied the method by [8] to calculate the power and capacity factors for the seven tourist seasons and eight turbine types. Our study revealed that interannual variability in wind speed at hub height can cause differences in produced power that are of the order of the differences among turbine types with similar hub height.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we consider a natural coordinate frame with the unit vectors s t , s n , and s b that form a righthanded rectangular coordinate system at any given point of a curve in space (moving trihedron) like a trajectory or a streamline (see Figure 3), where the subscript s characterizes the streamline-related quantities. The velocity vector at a given point along the streamline is given by [56]). Even though air density is considered as spatially constant, Bernoulli's equation can often be applied to atmospheric flows.…”
Section: The Bernoulli Equationmentioning
confidence: 99%